What is the optimal education structure for improving diabetes control and minimizing distress in patients with type 2 diabetes?. Issue 11 (November 2017) - Colby, Benjamin; Auger, Armand
Abstract : EVIDENCE‐BASED ANSWER : Group‐based and individual‐based diabetes education reduces glycosylated hemoglobin (HbA1C) slightly more than routine provider visits, with greater effect seen in patients with higher baseline HbA1C (SOR: C, meta‐analyses of RCTs and single cohort study with disease‐oriented evidence). The differences in HbA1C between individual and group education at 6 months are inconsistent, but no difference is apparent after 12 months (SOR: C, inconsistent meta‐analysis of RCTs and single RCT with disease‐oriented outcomes). Less time‐intensive individual sessions monthly are slightly better than more time‐intensive group sessions weekly at reducing HbA1C and diabetes‐related distress (SOR: B, RCT).